2013
DOI: 10.1016/j.ihj.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The report on the Indian coronary intervention data for the year 2011 – National Interventional Council

Abstract: The National interventional council of Cardiological Society of India has conventionally been presenting the data on various forms of cardiac interventions performed in the previous year at its annual meeting. Here we are reporting the data on coronary interventions done in India during the year 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…are the major determinants in making of this epidemiological picture. Also, as per the report of National Interventional Cardiology (NIC), 2011 for data on Indian coronary heart disease, 13.6% of patients were below 40 years of age [17]. Almost one quarter i.e.…”
Section: Discussionmentioning
confidence: 94%
“…are the major determinants in making of this epidemiological picture. Also, as per the report of National Interventional Cardiology (NIC), 2011 for data on Indian coronary heart disease, 13.6% of patients were below 40 years of age [17]. Almost one quarter i.e.…”
Section: Discussionmentioning
confidence: 94%
“…In resource-crunched settings like rural India, where Cath Lab facilities are scarce, thrombolytic therapy is still an important part of the early treatment of STEMI. (2,3,4) The advent of percutaneous intervention strategies and advance of bypass graft surgeries has made thrombolysis a very rarely done therapy. In this study, a longterm outcome of thrombolytic therapy was analysed and was found to be of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…27 In 2011, >152,000 percutaneous coronary interventions were performed in India with approximately 194,000 stents deployed compared to 40,000 coronary interventions in 2005. 28 In China, data from 2009 suggest that nearly 240,000 percutaneous coronary interventions were performed, with >247,000 stents deployed compared to only about 16,000 percutaneous coronary interventions in 2001. 28-30 The number of people in whom dual antiplatelet therapy is indicated is thus similarly increasing.…”
Section: Rationale For Adding Clopidogrel To the Model List Of Essentmentioning
confidence: 99%